10 Steps for Changing Your Life - Pinkoon, Damrong (2016)
An ordinary person doesn’t need to be a genius to change themselves to become better. They just have to know how to push themselves to change themselves. They have to believe the words ‘God helps those who help ourselves more than…ourselves and nobody in this world can change other.